2017
DOI: 10.1111/evo.13225
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression maintained by recessive lethal mutations interacting with stabilizing selection on quantitative characters in a partially self-fertilizing population

Abstract: The bimodal distribution of fitness effects of new mutations and standing genetic variation, due to early-acting strongly deleterious recessive mutations and late-acting mildly deleterious mutations, is analyzed using the Kondrashov model for lethals (K), with either the infinitesimal model for selfing (IMS) or the Gaussian allele model (GAM) for quantitative genetic variance under stabilizing selection. In the combined models (KIMS and KGAM) high genomic mutation rates to lethals and weak stabilizing selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Templeton & Read () suggested that a short period of intense inbreeding could rapidly purge inbreeding depression from a population. Although their empirical findings on purging are no longer considered reliable (Willis & Wiese, ), theory predicts that purging will most readily occur when inbreeding depression is primarily composed of a small number of lethal or near‐lethal recessive mutations (Charlesworth & Willis, ; Lande & Porcher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Templeton & Read () suggested that a short period of intense inbreeding could rapidly purge inbreeding depression from a population. Although their empirical findings on purging are no longer considered reliable (Willis & Wiese, ), theory predicts that purging will most readily occur when inbreeding depression is primarily composed of a small number of lethal or near‐lethal recessive mutations (Charlesworth & Willis, ; Lande & Porcher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Only modest effects of such interference among slightly deleterious mutations on levels of inbreeding depression in partially selfing populations have been found for multiplicative fitness models with dominance coefficients of the magnitude assumed here (Bersabé, Caballero, Pérez‐Figueroa, & García‐Dorado, ; Charlesworth, Morgan, & Charlesworth, ; Kamran‐Disfani & Agrawal, ; Roze, ), unless the population size is very small. Larger effects of interference may occur for the small dominance coefficients ( h ≤ 0.02) associated with severely deleterious or recessive lethal mutations (Kelly, ; Lande, ; Lande & Porcher, ; Porcher & Lande, ), leading to much higher frequencies of deleterious mutations than expected in the absence of interference, but the low values of B in most studies in Table suggest that the contributions from such mutations are minor. Indeed, they are likely to be purged from partially inbreeding populations, unless mutation rates are very high (Kelly, ; Lande & Schemske, ).…”
Section: Discussionmentioning
confidence: 99%
“…Only modest effects of such interference among slightly deleterious mutations on levels of inbreeding depression in partially selfing populations have been found for multiplicative fitness models with dominance coefficients of the magnitude assumed here (Bersabé, Caballero, Pérez-Figuereoa, & García-Dorado, 2016;Charlesworth, Morgan & Charlesworth, 1992;Kamran-Disfani & Agrawal, 2014;Roze, 2015), unless the population size is very small. Larger effects of interference may occur for the small dominance coefficients (h ≤ 0.02) for severely deleterious or recessive lethal mutation (Kelly, 2007;Lande, 1994;Lande & Porcher, 2017;Porcher & Lande, 2016), leading to much higher frequencies of deleterious mutations than expected in the absence of interference, but the low values of B in most studies in Table S2 suggest that the contributions from such mutations are minor. Indeed, they are likely to be purged from partially inbreeding populations, unless mutation rates are very high (Lande & Schemske, 1985;Kelly, 2007).…”
Section: Caveats and Complicationsmentioning
confidence: 98%